'Niña somebody': Bringing Elena Fortún's Celia to Spanish television. Issue 1 (1st March 2015) - Vernon, Kathleen M.
In much of his varied career, José Luis Borau vowed he would never work on television, undertake the adaptation of a literary work or direct a historical film. Yet, in 1991, in collaboration with his long-time friend and novelist Carmen Martín Gaite, Borau took on the task of producing and directing a television series based on the popular children's books of Republican-era writer Elena Fortún. Told from the perspective of the precocious 7-year-old protagonist Celia Gálvez, the series offers a glimpse into the world of the pre–Civil War Madrileñan bourgeoisie. Although the child of privilege, Celia insistently questions accepted hierarchies, from gender roles and class divisions to the dominant role of religion. Born from Borau's conviction that children deserve the best in cultural offerings, the series also marked an opportunity to revisit their own childhoods and childhood readings for the director and his co-scriptwriter Martín Gaite.